Healthcare Workers and Life Satisfaction during the Pandemic - Chiara Costi; Andrew E. Clark; Anthony Lepinteur; Conchita D'Ambrosio (Institute of Labor Economics (IZA), 2023)
We evaluate the effect of the COVID-19 pandemic on the life satisfaction of healthcare workers, as compared to the wider workforce, in five European countries. In ten waves of quarterly panel data, the life satisfaction of healthcare workers is always higher than that of other essential workers and non-essential workers. Life satisfaction follows a double humped pattern over time for all workers, which is largely explained by the COVID-19 death rate and policy stringency. The spread of the pandemic in terms of the death rate has twice as large an effect on healthcare workers' life satisfaction; on the contrary, the latter are the only workers whose satisfaction was not affected by the stringency of lockdown policies.
Keywords: H51; I18; I31; 330; healthcare workers; life satisfaction; COVID-19; policy stringency